Training for making garden lights with solar energy sources - Diana Lestariningsih; Albert Gunadhi; Lanny Agustine; Widya Andyardja (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Curah Cottok Village, Kapongan District, Situbondo Regency, East Java has a hill which is an empty and barren land with scorching sun rays from morning until afternoon. The hill was planned by Mr. Muh Samsuri Abbas as the Village Head as a tourist spot. The conditions of the hot area are very suitable for solar power technology applications. To support the realization of a tourist spot and take advantage of the scorching weather with sunshine, community service activities were carried out by providing training in making garden lights. To activate the garden lights using solar energy. Garden lights with solar power consist of 5-watt DC lights, 10A BCR, 7AH batteries, 10WP solar panels. There were 32 participants who were divided into 5 groups. Participants were dominated by young adults. The results of the participant's activity are 5 garden lights with solar power that have been installed on the Curah Cottok hill. The garden lights function well by illuminating the top of the Curah Cottok hill at night.